PENGARUH SUBTITUSI SARI BUAH SEMANGKA (Citrullus lanatus) DALAM PENGENCER SITRAT- KUNING TELUR TERHADAP KUALITAS SPERMATOZOA SAPI BALI (Effect of watermelon juice supplementation in citrate - egg yolk extender on spermatozoa quality of bali bulls) - Maria M. Bria; Wilmientje M. Nalley; Thomas M. Hine; Johny N. Kihe (JURNAL NUKLEUS PETERNAKAN, 2022)
This study aims to determine the effect of adding watermelon juice (WJ) into citrate-egg yolk (C-EY) diluents on the spermatozoa quality of bali catlle. Semen was collected twice a week using an artificial vaginal method of three bali bulls with normal body condition and reproductive organs. Semen that has motility > 70%, concentration >1000 x 106 and abnormalities ≤ 20 % was used in this study. Semen then divided into five treatments: C-EY 100% (T0), C-EY-25% WJ (T1), C-EY-50% WJ (T2), C-EY-75% WJ (T3), WJ 100% (T4) and then stored in a refrigerator at temperature 3-5oC. The quality of spermatozoa was evaluated every 24 hours for sperm motility, viability, and abnormalities. The results showed that spermatozoa diluted with S-KT supplemented with 75% WJ (T3) had a higher quality (P<0,05) compared to the other treatments, with motility 40,53 %, viability 47,35%, and abnormalities 4,21% on the 6th day of preservation. It was concluded that the addition of WJ to C-EY diluent was able to maintain the quality of bali bull spermatozoa, with the best SBS concentration is 75%.